"It's all about trust": reflections of researchers on the complexity and controversy surrounding biobanking in South Africa. Issue 1 (December 2016) - Moodley, Keymanthri; Singh, Shenuka
Abstract Background Biobanks are precariously situated at the intersection of science, genetics, genomics, society, ethics, the law and politics. This multi-disciplinarity has given rise to a new discourse in health research involving diverse stakeholders. Each stakeholder is embedded in a unique context and articulates his/her biobanking activities differently. To researchers, biobanks carry enormous transformative potential in terms of advancing scientific discovery and knowledge. However, in the context of power asymmetries in Africa and a distrust in science born out of historical exploitation, researchers must balance the scientific imperative of collecting, storing and sharing high quality biological samples with obligations to donors/participants, communities, international collaborators, regulatory and ethics authorities. To date, researcher perspectives on biobanking in South Africa have not been explored and documented. Methods In-depth qualitative interviews were conducted with a purposive sample of 21 researchers – 8 in the Western Cape, 3 in Gauteng and 10 in Kwa-Zulu Natal. Interviews lasted approximately 40–60 min and were audiotaped with consent. Thematic analysis of the transcribed interviews was conducted by the co-authors. Results Researchers articulated serious concerns over standardised regulatory approaches that failed to consider the heterogeneity of biobanks. Given that biobanks differ considerably, guidelines and RECs need to stratify risk accordingly and governance processes and structures must be flexible. While RECs were regarded as an important component of the governance structure researchers expressed concern about their expertise in biobanking. Operational management of biobanks was regarded as an ethical imperative and a pre-requisite to building trust during consent processes. While broad general consent was preferred, tiered consent was thought to be more consistent with respect for autonomy and building trust. Material Transfer Agreements (MTAs) were often lacking when biosamples were exported and this was perceived to impact negatively on trust. On the other hand, researchers believed that authentic community engagement would help to build trust. Conclusion Building trust will best be achieved via a system of governance structures and processes that precede the establishment of a biobank and monitor progress from the point of sample collection through to future use, including export. Such governance structures must be robust and must include comprehensive national legislation, policy and contextualised guidelines. Currently such governance infrastructure appears to be lacking in many African countries including South Africa. Capacity development of all stakeholders including REC members will enhance expeditious and efficient review of biobanking protocols which in turn will reinforce trust in the researcher-donor relationship. Science translation and community engagement in biobanking is integral to the success of biobanking in South Africa.